2018
DOI: 10.1159/000490934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P450 Oxidoreductase Polymorphisms on the Metabolic Activities of Ten Cytochrome P450s Varied by Polymorphic CYP Genotypes in Human Liver Microsomes

Abstract: Background/ Aims: Little is known about the effect of P450 oxidoreductase (POR) gene polymorphisms on the activities of CYPs with multiple genotypes. Methods: We genotyped 102 human livers for 18 known POR single nucleotide polymorphisms (SNPs) with allelic frequencies greater than 1% as well as for 27 known SNPs in 10 CYPs. CYP enzyme activities in microsomes prepared from these livers were determined by measuring probe substrate metabolism by high performance liquid chromatograph. Results: We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…As a cell line originating from a human hepatoblastoma this was not quite clear for HepG2, since cells could adapt their phenotype due to genetic instability typical for cancer cells. For primary-like hepatocytes, however, this observation supports the finding from earlier studies that these cell models remain functionally active over a longer cultivation period than is the case for cultivated primary human hepatocytes [12,13,17]. Interestingly, cancer cell line HepG2 cells showed significantly increased POR expression at both gene and protein levels compared to primary-like hepatocytes.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As a cell line originating from a human hepatoblastoma this was not quite clear for HepG2, since cells could adapt their phenotype due to genetic instability typical for cancer cells. For primary-like hepatocytes, however, this observation supports the finding from earlier studies that these cell models remain functionally active over a longer cultivation period than is the case for cultivated primary human hepatocytes [12,13,17]. Interestingly, cancer cell line HepG2 cells showed significantly increased POR expression at both gene and protein levels compared to primary-like hepatocytes.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, primary human hepatocytes (pHHs) are the "gold standard" for in vitro studies on hepatic metabolism, clearance, hepatotoxicity and drug-drug interaction [9]. However, this research is still restricted by pHH scarcity, donor variability and their rapid dedifferentiation in vitro [10][11][12][13][14]. An inflammatory response by endotoxin contamination [15,16] originating from bacterial collagenase preparations, loss of normal cell polarity when dissolving them from liver tissue or down-regulation of liver-specific transcription factors influencing phase I/II protein expression were discussed as possible causes [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the physiological and pathological activity of CYP2E1, we previously found that CYP2E1‐mediated probe clearance increased remarkably in hepatofibrotic tissue and positively correlated with enzyme velocity for DEN metabolism. CYP2E1‐mediated probe drug clearance showed intraindividual variation in patients with hepatofibrosis, and the difference in the metabolism of DEN by CYP2E1 may be the cause of hepatofibrosis . Herein CYP2E1 activity was determined by measuring the enzyme velocity for DEN metabolism in human hepatofibrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Another best example is mutation of p450 oxidoreductase (POR) gene, which leads to insufficiency of P450 enzymes characterized by defective steroidogenesis. Similarly, deficiency of mitochondrial acetaldehyde dehydrogenase disturbs normal metabolism of alcohol and leads to accumulation of acetaldehyde [8,15,16]. These conditions in turn affect the normal development and reproduction.…”
Section: Introductionmentioning
confidence: 99%